(untitled) (Forum Agribisnis, 2025)
Indonesia is one of the primary exporters of coffee commodities. The majority of Indonesia’s coffee production is exported abroad, while the remainder serves domestic demand. Indonesian coffee exports span five continents: Asia, Africa, Australia, the Americas, and Europe, with the main market share in Europe. This research aims to achieve two objectives: (1) analyze Indonesia’s market share in international coffee bean exports, and (2) assess Indonesia’s position in the international coffee market using the Almost Ideal Demand System (AIDS) approach. The study utilizes secondary data in the form of monthly time series spanning 12 years from 2010 to 2021, focusing on HS code 0901111 (coffee, not roasted, not decaffeinated). The research findings reveal that the average market share of Indonesian coffee bean exports in the international market is approximately 6%, positioning Indonesia third after Brazil and Colombia. This share is greater than that of Guatemala, Ethiopia, Uganda, and other exporting nations. The price elasticity of demand for coffee in Indonesia (uncompensated) is negative, specifically -0.35, indicating inelasticity (since it is less than 1). Additionally, the cross-price elasticity between Indonesia and Brazil, Colombia, Guatemala, Ethiopia, and Uganda is also negative, with respective values of 0.16, 0.32, 0.20, 0.07, and 0.02. These values suggest a complementary relationship. Furthermore, the expenditure elasticity of Indonesian coffee exports is negative, implying that Indonesian coffee falls into the category of inferior goods, with a value of 1.143, which is greater than 1, signifying elasticity.